Complete chromosome and plasmid sequences of two plant pathogens, Dickeya solani strains D s0432-1 and PPO 9019 - Khayi, Slimane; Blin, Pauline; Chong, Teik Min; Chan, Kok Gan; Faure, Denis (American Society for Microbiology, 2018)
Dickeya solani species are emerging bacterial pathogens of Solanum tuberosum. Here, we announce the complete genome sequences of two strains, Dickeya solani D s0432-1 and PPO 9019. Strain PPO 9019 represents the first described member of the genus Dickeya with an extrachromosomal genetic element.